2016
DOI: 10.1177/0959683616632892
|View full text |Cite
|
Sign up to set email alerts
|

Late-Holocene gallery forest retrogression in the Venezuelan Guayana: New data and implications for the conservation of a cultural landscape

Abstract: Fire is considered a major threat to forest conservation in the Neotropics. Palaeoecological studies are critical for understanding the long-term interactions of climate, fire, and human activities in the savanna-forest dynamic. Here, new data from palynological analyses conducted in sedimentary records from the northern edge of the Amazon Basin, the Gran Sabana, southeast of Canaima National Park (CNP) are presented. Four radiocarbon ages from Quebrada Kowana (QK) and two for Ariwe Fernland (AF) records showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…In the Gran Sabana of Venezuela and likely in the contiguous Roraima savannas of Brazil (e.g., BVI), the gallery forest was more dominant than the savannas 3,100-1,800 Cal yr BP (Leal et al, 2016). bility that it has adapted to re-colonizing habitats disrupted by fire.…”
Section: Insights Of Influence Of Human Management On Genetic Divermentioning
confidence: 99%
“…In the Gran Sabana of Venezuela and likely in the contiguous Roraima savannas of Brazil (e.g., BVI), the gallery forest was more dominant than the savannas 3,100-1,800 Cal yr BP (Leal et al, 2016). bility that it has adapted to re-colonizing habitats disrupted by fire.…”
Section: Insights Of Influence Of Human Management On Genetic Divermentioning
confidence: 99%
“…First, in ecological and paleoecological sciences, the idea that South American savannas resulted from the degradation of forests due to fire (Dezzeo et al., ; Rull et al, ), especially in the savannas of the Amazon basin, was used by fire‐fighting public bodies to maintain suppression policies. This was done without taking in consideration the value of traditional Indigenous knowledge as a sustainable tool for fire management and the complex interactions between fire and ecosystem dynamics (Bilbao et al., ; Leal et al, ). The idea of savannas as “degraded lands” promotes deforestation of these ancient ecosystems, and serves as a type of “green legitimisation” to expand soybean and more recently eucalyptus plantations across already threatened traditional territories and protected areas (Bond, ).…”
Section: Resistances and Limitsmentioning
confidence: 99%
“…Since fire is considered to be one of the key risk factors in the Gran Sabana (Bilbao and Vessuri 2006), the project also initiated a paleoecological reconstruction of the landscape history (Leal 2010, Leal et al 2016, an analysis of changes in the vegetation cover and land uses, and a study of fire behavior and its impacts in the Gran Sabana (Bilbao et al 2009(Bilbao et al , 2010 [2] . Results of these studies were presented and discussed at various community assemblies that were part of the joint research activities, which prompted important discussions about the historical and social factors that have caused landscape change in the area.…”
Section: Researching Risk Factorsmentioning
confidence: 99%
“…Likewise, the paleoecological reconstruction of the history of the Gran Sabana landscape revealed that in contrast to what has been commonly assumed, fire has been a permanent component of the Gran Sabana landscape for the last 7000 years (Leal 2010, Leal at al. 2016, similar to what has been reported in the Cerrado savannas in Brazil (Mistry et al 2005).…”
Section: Social Validation Of Local Knowledge Of Firementioning
confidence: 99%
See 1 more Smart Citation